Ethernet-Based Servo-Hydraulic Real-Time Controller and DAQ at ELSA for Large Scale Experiments. Issue 15 (18th November 2022) - Peroni, Marco; Pegon, Pierre; Molina, Francisco Javier; Buchet, Philippe
ABSTRACT: This paper presents an overview of the developments performed at the European Laboratory for Structural Assessment (ELSA) of the Joint Research Centre of European Commission concerning the new generation of servo-hydraulic real-time digital controller/acquisition system adopted in large scale experiments. The hardware architecture is based on EtherCAT® modules that guarantee a versatile and modular system easily adaptable to changing requirements (a typical situation experienced at ELSA with custom adapted non-standardized large scale structural experiments). Other fundamental features of this system are that all the analog signals are digitalized in the proximity of the transducers reducing noise-to-signal ratio (a great advantage for Pseudo-dynamic tests but in general for all experimentation), and all the different slave controllers communicate at each time sampling through a deterministic robust digital bus. In addition to the increasing computer performances, the developed simplified software architecture does offer a substantial improvement of control quality in terms of speed, safety, and accuracy compared with conventional/commercial systems.